2020
DOI: 10.3389/fvets.2020.00563
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid as an Antimicrobial for Poultry Production: A Review

Abstract: Organic acids continue to receive considerable attention as feed additives for animal production. Most of the emphasis to date has focused on food safety aspects, particularly on lowering the incidence of foodborne pathogens in poultry and other livestock. Several organic acids are currently either being examined or are already being implemented in commercial settings. Among the several organic acids that have been studied extensively, is formic acid. Formic acid has been added to poultry diets as a means to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 146 publications
(264 reference statements)
0
42
0
1
Order By: Relevance
“…Other researchers have found similar reductions in IgA, IgG and IgM concentrations when infected broilers were treated with herb polysaccharide extracts 43 ; however, in our study no impact was observed on IgG levels. Intestinal immunity is also involved in preventing inflammation 44 through the biosynthesis of short chain fatty acids (SCFA), wellknown for their antagonistic effect against pathogenic bacteria and parasites 45,46 . Our study shows that the total SCFA levels are reduced in the presence of E. tenella when either AG or ROB treatment is applied, an observation previously described when infected broilers received a nucleotide-rich yeast extract 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have found similar reductions in IgA, IgG and IgM concentrations when infected broilers were treated with herb polysaccharide extracts 43 ; however, in our study no impact was observed on IgG levels. Intestinal immunity is also involved in preventing inflammation 44 through the biosynthesis of short chain fatty acids (SCFA), wellknown for their antagonistic effect against pathogenic bacteria and parasites 45,46 . Our study shows that the total SCFA levels are reduced in the presence of E. tenella when either AG or ROB treatment is applied, an observation previously described when infected broilers received a nucleotide-rich yeast extract 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, organic acids have the potential to inhibit E. coli infection [ 94 ], and a supplementation with 2% citric acid can improve the gut health [ 95 ]. It has been reported that formic acid, an extensively studied organic acid, can limit Salmonella infection and other foodborne pathogens when used in a poultry diet [ 96 ]. Several organic acids may also play beneficial roles in digestion.…”
Section: Possibilities Of Antibiotic-free Broiler Productionmentioning
confidence: 99%
“…However, a more pronounced effect might have been observed if a longer contact time had also been trialled, as reported by Iba and Berchieri [ 24 ]. The degree of efficacy that might be observed more generally with OA-based treatments will depend on the particular circumstances of product and feed composition and probably other factors such as moisture, temperature and natural versus experimental contamination of feed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%